Bacterial-binding dressings in the management of wound healing and infection prevention: a narrative review. (2nd June 2019) - Chadwick, Paul; Ousey, Karen
Abstract : The aim of this review was to present the clinical data on the use of the family of bacterial-binding dressings (Sorbact; dialkylcarbamoyl chloride-coated) in the treatment of a variety of acute and chronic wounds. The findings are discussed in terms of the effectiveness of the bacterial-binding dressings on bacterial bioburden reduction, infection prevention, initiation/progression of wound healing and cost-effectiveness. The evidence in support of the bacterial-binding dressings is strongest in the area of infection prevention in surgical wounds, with several controlled trials showing the prophylactic benefit of the dressing in these wounds. Wound bioburden management in chronic wounds is supported by a number of clinical studies. In total, 29 published clinical studies (with a total of 4044 patients) were included in this review.